Soldiers and the Soviet State : Civil-Military Relations from Brezhnev to Gorbachev. - Colton, Timothy J. (Princeton legacy library., 2014)
How much power does the Soviet military exert on the politics of the Kremlin? This is one of the most controversial questions in the study of the Soviet Union, here addressed by eight top Western specialists on Soviet politics and security policy. While the authors assert that the civil-military relationship has been less turbulent than often believed, they also point out that Gorbachev's reforms threaten the system of buffers that have until now shielded the military-industrial world from disruption and change. Introduced by Timothy Colton's essay, ""Perspectives on Civil-Military Re